PENINGKATAN KREATIVITAS MELALUI BERMAIN KONSTRUKTIF DENGAN MEDIA KOKORU - Roselina, Donna; Nasirun, H. M.; Wembrayarli, Wembrayarli (Jurnal Ilmiah Potensia, 2018)
The problem of this study is what does the constructive play activity by using kokoru media can improve the early childhood’s creativity at Group BI of PAUD Islam Intan Insani of Bengkulu City. The objectives of this study was to know the improving of creativity of early childhood through constructive play by using kokoru media. The method used of this research was Classroom Action Research, by conducted in two cycles, each cycle was conduted in three meetings. The subject were all child at Group BI of PAUD Islam Intan Insani of Bengkulu City which were 17 child consists of 11 male and 6 female. The techique of collecting data was observation technique. With the average scoring and were used as the technique of analysis data. The result of this study was proved that mastery learning outcomes throug constructive play by using kokoru media can improve the child’s creativity. In the final result was shown the children’s creativity ability was clasically. From the result of this study it might be a recommended reference to the future study that by using kokoru media is not only improve the creativity but also the child’s fine motor.